2007
DOI: 10.1073/pnas.0709453104
|View full text |Cite
|
Sign up to set email alerts
|

Delayed leaf senescence induces extreme drought tolerance in a flowering plant

Abstract: Drought, the most prominent threat to agricultural production worldwide, accelerates leaf senescence, leading to a decrease in canopy size, loss in photosynthesis and reduced yields. On the basis of the assumption that senescence is a type of cell death program that could be inappropriately activated during drought, we hypothesized that it may be possible to enhance drought tolerance by delaying droughtinduced leaf senescence. We generated transgenic plants expressing an isopentenyltransferase gene driven by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
598
1
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 787 publications
(636 citation statements)
references
References 40 publications
28
598
1
9
Order By: Relevance
“…ABA-activated SnRK2s then mediate leaf senescence by phosphorylation of Related to ABA-Insensitive 3/VP1 (RAV1) and ABF2 transcription factors, which then up-regulate the expression of ORE1 and other NAC transcription factors, thereby activating expression of SAGs. Previous research has suggested that transgenic plants with delayed leaf senescence are more resistant to drought stress (1). However, we examined the importance of ABA-induced leaf senescence under drought stress and found that the increased leaf senescence in pRD29A::PYL9 transgenic plants apparently helps generate a greater osmotic potential gradient, which causes water to preferentially flow to developing tissues.…”
Section: Significancementioning
confidence: 86%
See 1 more Smart Citation
“…ABA-activated SnRK2s then mediate leaf senescence by phosphorylation of Related to ABA-Insensitive 3/VP1 (RAV1) and ABF2 transcription factors, which then up-regulate the expression of ORE1 and other NAC transcription factors, thereby activating expression of SAGs. Previous research has suggested that transgenic plants with delayed leaf senescence are more resistant to drought stress (1). However, we examined the importance of ABA-induced leaf senescence under drought stress and found that the increased leaf senescence in pRD29A::PYL9 transgenic plants apparently helps generate a greater osmotic potential gradient, which causes water to preferentially flow to developing tissues.…”
Section: Significancementioning
confidence: 86%
“…In plants, leaf senescence increases the transfer of nutrients to developing and storage tissues. Recently, studies on transgenic tobacco showed that delayed leaf senescence increases plant resistance to drought stress (1). However, the senescence and abscission of older leaves and subsequent transfer of nutrients are known to increase plant survival under abiotic stresses, including drought, low or high temperatures, and darkness (2,3).…”
mentioning
confidence: 99%
“…They involve regulatory molecules, TFs and hormones such as ABA, cytokinin (CK), ethylene and their crosstalk mechanisms (Peleg and Blumwald 2011). Among these, the CKinduced delayed senescence has been shown to be effective in increasing the tolerance of plants to water deficit (Rivero et al 2007). Transgenic plants expressing the IPT gene, encoding a key enzyme in CK synthesis, under the control of SARK (a stress-and maturity-induced promoter) displayed enhanced photosynthesis and high yields under water stress (Rivero et al 2007;Peleg et al 2011b;Reguera et al 2013).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Among these, the CKinduced delayed senescence has been shown to be effective in increasing the tolerance of plants to water deficit (Rivero et al 2007). Transgenic plants expressing the IPT gene, encoding a key enzyme in CK synthesis, under the control of SARK (a stress-and maturity-induced promoter) displayed enhanced photosynthesis and high yields under water stress (Rivero et al 2007;Peleg et al 2011b;Reguera et al 2013). A Gene expression profile of flag leaves from wild-type plants and transgenic rice plants expressing P SARK ::IPT, highlighted the differential expression of OsWRKY47 in the P SARK ::IPT plants under water stress (Peleg et al 2011b).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…This might be due to fewer known genes and QTL. Until now, the isopentenyl transferase (IPT) gene (Gan and Amasino 1995) has been the most successful application of improving stay-green traits and delayed senescence for increasing productivity in specific crops (Rivero et al 2007;Swartzberg et al 2006), but it does not affect grain yield in wheat (Sykorova et al 2008).…”
Section: Relationship Between Stay-green and Agronomic Traitsmentioning
confidence: 99%